1975
DOI: 10.1104/pp.55.4.658
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Glucose 6-Phosphate Dehydrogenase in Blue-Green Algae

Abstract: Glucose 6-phosphate dehydrogenase (EC 1. 1.1. 49) has been partially purified from Anacystis nidulans and Anabaena flos-aquae by means of anmnonium sulfate fractionation and exclusion gel chromatography and the kinetic properties de-termined.Glucose 6-phosphate dehydrogenase from these blue-green algae exhibits Michaelis-Menten kinetics at pH 6.7. At this pH, Km values of 0.37 mM for glucose 6-phosphate and 10 zM for NADP were determined. At a pH above 7.4, the enzyme exhibits sigmoidal kinetics with respect t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

1976
1976
1989
1989

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 24 publications
2
32
0
Order By: Relevance
“…A block in glucose-6-P metabolism in the light has been demonstrated and the kinetics of this blockage investigated (6). Additional evidence that refixation of CO2 is not a major factor is provided by light saturation experiments (data not shown) in which the inhibition of glucose-6-P turnover is maximal at a light intensity much lower than that which supports appreciable CO2 fixation.…”
Section: Methodsmentioning
confidence: 64%
See 3 more Smart Citations
“…A block in glucose-6-P metabolism in the light has been demonstrated and the kinetics of this blockage investigated (6). Additional evidence that refixation of CO2 is not a major factor is provided by light saturation experiments (data not shown) in which the inhibition of glucose-6-P turnover is maximal at a light intensity much lower than that which supports appreciable CO2 fixation.…”
Section: Methodsmentioning
confidence: 64%
“…Our CO2 fixation studies suggested the efficacy of this approach. The stimulation of CO2 fixation in Anabaena by glucose-6-P is promising since this compound has been implicated as an important branch point intermediate in blue-green algae, with its turnover being controlled by some product(s) of photosynthesis (6,16). Our goal, therefore, is to demonstrate that glucose-6-P enters Anabaena cells intact, turns over in a manner consistent with previous studies on in vivo pool size changes (8,13), and affects several physiological functions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rather it seems more likely that glucose-6-P dehydrogenase may be inactivated within the chloroplast by the LEM and inhibited by NADPH. It is interesting to note that the enzyme from Anacystis nidulans is inactivated by light (7) and, like the higher plant chloroplastic enzyme, sensitive to NADPH (8).…”
Section: Resultsmentioning
confidence: 99%